A co-templating route to the synthesis of Cu SAPO STA-7, giving an active catalyst for the selective catalytic reduction of NO - Picone, Andrea Lorena (2011)
Copper cyclam (cyclam = 1,4,8,11-tetraazacyclotetradecane) and tetraethylammonium (TEA+ ) act as cotemplates for the hydrothermal crystallisation of the silicoaluminophosphate SAPO STA-7, as determined by UV–visible, ESR and solid-state MAS NMR spectroscopies, powder and single crystal X-ray diffraction and chemical analysis. Calcination of the as-prepared solid in flowing oxygen removes all organics to leave Cu(II),H-SAPO STA-7 (hereafter Cu-SAPO STA-7) in which the presence of bridging hydroxyl groups is confirmed by IR and the presence of multiple environments for Cu2+ is shown by IR using NO as a probe molecule. Rietveld analysis of synchrotron X-ray powder diffraction data collected over the temperature range 293–673 K locates Cu2+ cations distributed over four sites: above six membered rings (6MRs) and in the three different 8MR windows of the STA-7 structure. Cu-SAPO STA-7 is a very good catalyst for the selective catalytic reduction of NO with NH3, in the presence or absence of water vapour, so that this approach represents an efficient and effective route to copper-containing SAPO catalysts that obviates the need for an aqueous Cu2+ ion exchange step during preparation.